2021
DOI: 10.3390/molecules26020332
|View full text |Cite
|
Sign up to set email alerts
|

Physicochemical Characterization, Antioxidant Capacity, and Sensory Properties of Murici (Byrsonima crassifolia (L.) Kunth) and Taperebá (Spondias mombin L.) Beverages

Adriana Aniceto,
Julia Montenegro,
Rafael da Silva Cadena
et al.

Abstract: Amazonian fruits are excellent sources of bioactive compounds and can be used in beverages to improve the nutritional and sensorial characteristics. The present study aimed to develop a blend of murici (Byrsonima Crassifolia (L.) Kunth) and taperebá (Spondias Mombin L.) through experimental design and investigating the nutritional and sensorial characteristics of fruits and beverages. The murici was highlighted as higher vitamin C content (58.88 mg · 100 g−1) compared to taperebá (25.93 mg · 100 g−1). The muri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 33 publications
(29 reference statements)
0
18
0
Order By: Relevance
“…In this study, the authors verified that the dry pulp of taperebá presented a higher content of phenolic compounds (TP) (712.72 ± 8.71 µg/g) when compared to other fruits, such as açaí-do-Amazonas (264.53 ± 10.56 µg/g) (Euterpe precatoria). Aniceto et al (2021) [8] also found a similar trend in the values of phenolic compounds from taperebá (~1300 mg GAE/100 g of commercial frozen pulp) when compared to murici (Byrsonima crassifolia (L.) Kunth, ~300 mg GAE/100 g of commercial frozen pulp). Another piece of research, carried out by Abiodun et al (2020) [30], quantified interesting values of phenolic compounds in taperebá seeds (Spondias mombin L.) (~240.00 GAE/g seed).…”
Section: Quantification Of Total Phenolics and Evaluation Of The Anti...mentioning
confidence: 67%
See 3 more Smart Citations
“…In this study, the authors verified that the dry pulp of taperebá presented a higher content of phenolic compounds (TP) (712.72 ± 8.71 µg/g) when compared to other fruits, such as açaí-do-Amazonas (264.53 ± 10.56 µg/g) (Euterpe precatoria). Aniceto et al (2021) [8] also found a similar trend in the values of phenolic compounds from taperebá (~1300 mg GAE/100 g of commercial frozen pulp) when compared to murici (Byrsonima crassifolia (L.) Kunth, ~300 mg GAE/100 g of commercial frozen pulp). Another piece of research, carried out by Abiodun et al (2020) [30], quantified interesting values of phenolic compounds in taperebá seeds (Spondias mombin L.) (~240.00 GAE/g seed).…”
Section: Quantification Of Total Phenolics and Evaluation Of The Anti...mentioning
confidence: 67%
“…The taperebá (Spondias mombin L.), also called cajá, cajá verdadeiro and cajá-mirim, is a member of the Anacardiaceae family and can be found in tropical areas of America, Asia and Africa, presenting as a small ovoid drupe with thin yellowish skin and a bittersweet taste [5]. This wild fruit from the Cerrado has shown important characteristics, due to the significant content of some phenolic compounds [6][7][8][9], demonstrating biological effects such as cytotoxic activity in ovarian cancer cells [9], gastroprotective action in rats [10] and antioxidant ability [8].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In Brazil, the biodiversity of native fruits represents an important source of vitamins. The cultivation and consumption of especially exotic fruits are increasing in local and international markets, holding a potential interest due to the recognition of their nutritional and therapeutic value [2]. In addition, the appreciation of native exotic fruits brings benefits to family farming and consequently contributes to the improvement of global food and nutritional security [3] due to the high content of bioactive molecules present in the fruits.…”
Section: Introductionmentioning
confidence: 99%